Digital Empowerment: The Sustainable Development of Chengdu Lacquerware’s Colors and Decorations - Jianhua Lyu; Qin Xu; Chuxiao Hu; Ming Chen (Applied Sciences)
The preservation and innovation of traditional craftsmanship under industrialization pressures constitute critical challenges for cultural sustainability. Focusing on Chengdu lacquerware—a Chinese intangible cultural heritage facing multifaceted preservation dilemmas—this study develops a digital methodology for its systematic documentation and contemporary adaptation. Through computational analysis of 307 historical artifacts spanning four craftsmanship categories (carved silver mercer, carved lacquer hidden flower, carved filling, and broach needle carving), we established a three-phase digital preservation framework: (1) image preprocessing of 280 qualified samples using adaptive binarization and Canny edge detection for ornament extraction, (2) chromatic analysis via two-stage K-means clustering to decode traditional color schemes, and (3) creation of a digital repository encompassing color profiles and ornamental elements. The resource library facilitated three practical applications: modular recombination of high-frequency motifs, cross-media design adaptations, and interactive visualization of craftsmanship processes. Technical analysis confirmed that adaptive binarization effectively mitigated image noise compared to conventional methods, while secondary clustering enhanced color scheme representativeness. These advancements demonstrate that structured digital archiving coupled with computational analysis can reconcile traditional aesthetics with modern design requirements without compromising cultural authenticity. The workflow provides a transferable model for intangible heritage preservation, emphasizing rigorous documentation alongside adaptive reuse mechanisms.